School, Family, And Community Partnerships: Preparing Educators And Improving Schools - Epstein, Joyce (Westview Press, 2001)
How can teachers and administrators be prepared to create partnerships with families and communities? Nationwide, rhetoric in favor of parent involvement is high, but the quality of most programs still is low. Part of the problem is that most teacher education, administrative training, and other education of school professionals omit topics of school, family, and community partnerships. Instead, educators are prepared in limited ways to "deal with parents" when problems occur.This volume, based on twenty years of original research, addresses growing field of school, family, and community partnerships and offers an alternative approach. It is now possible to prepare teachers and administrators with a solid base of knowledge on partnerships. There are theoretical perspectives and results from research and development that should be shared with educators. As partners, parents and teachers share responsibility for the education and development of their children. Common messages and collaborative activities of home and school help to promote student success, prevent problems, or solve those that arise.The chapters in this volume provide a strong background to help educators in training and in schools think about, talk about, and then act to develop comprehensive programs of school, family, and community partnerships. Readers will be able to: Understand Epstein's theory of overlapping spheres of influence of families, schools, and communities to support children as students Study Epstein's framework of six types of involvement to create partnerships Review the research on the implementation and effects of partnerships Apply the theory, framework, and research in class projects and assignments Gather ideas for specific practices of partnership for use in elementary, middle, and high schools This collection is designed for use in courses of teacher education, preparation of school administrators, and other courses that prepare professionals to understand and to work in schools and with families and students. It is a definitive resource both in and out of the classroom with Comments, Questions to Discuss, Activities, and Field Experiences in each of the chapters.